Load Balancing Performance in Etherchannel Technology Using the VLAN Trunking Protocol (VTP) Method: Load Balancing Performance in Etherchannel Technology Using the VLAN Trunking Protocol (VTP) Method - Muhammad Zulfi Rahmanzi; Iskandar Fitri; Andri Aningsih (Jurnal Mantik, 2020)
Increasing the number of network technology users is functioned so that network performance increases, it is necessary to have a network renovation process. The results of previous studies, the use of Load Balancing on Etherchannel technology using the VTP (VLAN Trunking Protocol) method can maximize network performance. In this network topology, VLAN and Etherchannel technology has been configured so that the operation runs efficiently. Etherchannel protocol used in analyzing VTP network performance, namely PAgP and LACP. QoS analysis results for 1 hour, when all connected conditions have an average value of 1.8 Mb / s throughput and 8.1% packet loss. The second test of CORE_SW2 condition was turned off, got an average throughput of 1.8Mb / s and 8.2% packet loss. When testing all three Po1 line conditions is disconnected, the connection is multiplied to 2 lines. Po5 gets an average throughput of 15MB / s and packet loss of 23.15%, Po2 gets throughput of 1.8 Mb / s and packet loss of 8.7%. Then the influence of Etherchannel technology when the first and second conditions are classified as good, while the third condition throughput is classified as very good, but the packet loss generated is of medium condition.